Heat transfer in road pavement structure and identification of its layers thermal parameters = Wymiana ciepła w konstrukcji nawierzchni drogowej i identyfikacja parametrów materiałowych tworzących jej warstwy - Allawdin, Piotr; Połczyński, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A heat transfer problem for the road pavement system "layered plate - embankment - soil base" is formulated. There are suggested mathematical models and their realization with the use of finite element analysis and design software program by solving the layered plate on the ground foundation.
Keywords: nawierzchnia drogowa; wymiana ciepła; konstrukcja nawierzchni drogowej; pavement system; heat transfer problem; boundary conditions identification; road pavement system